A Dual Parent Perspective on Control and Performance in International Joint Ventures: Lessons From a Developing Economy - Luo, Yadong; Shenkar, Oded; Nyaw, Mee-Kau (Journal of International Business Studies, 2001)
This study compares the control-performance relationship for foreign versus local parents in international joint ventures in China. Transaction cost analysis is found more applicable to foreign than to Chinese parents. Both overall and specific controls are associated with performance for foreign parents, while only specific control is for Chinese parents. Under goal incongruity, Chinese parent control is associated with foreign parent dissatisfaction with venture performance, but not vice-versa. Having a majority stake improves performance from a foreign parent perspective, but not from that of the Chinese parent.